The effect of the environmental, organization culture factors on job satisfaction study of Royal Malaysian Police - Mohd Izhan, Ismail (2015)
There are many factors that led to low performance of police work. Organizations cannot achieve high competitive levels of customer service quality if their employees do not feel satisfied. In other words, for an organization to have satisfied customers, it must first have satisfied employees. Therefore, maintaining and enhancing job satisfaction is important in order to establish quality worker, workplace and the work itself. The purpose of this study is to investigate the relationship between organizational culture (loyalty, job challenges, citizen cooperation and social choesion) and job satisfaction; to analyze the relationship between environmental factors (supervision, salary and incentives, public perception, organization policy and strategy and promotion opportunity) and job satisfaction. The congruence model used, was inspired by combining the theories, in order to study the effects of culture and environment on job satisfaction. The data for this study were collected, using questionnaires from 350police officers in Malaysia, and was analyzed, using SPSS 17. Descriptive, reliability, T-test, correlation and regression analyses were run to test these hypotheses. The study found that loyalty, job challenges, salary and incentives, organization policy and strategy and promotion opportunity has a direct significant relationship and job satisfaction. Theoretical, practical and managerial implementations are also discussed, along with suggestions for future research avenues.